Handling false chronic kidney disease and diabetes treatment information - Sourabh Sharma; Himanshu Verma; Sanjay Kalra (Journal of the Pakistan Medical Association)
While examining the social perspectives of chronic kidney disease (CKD) and its most common cause, diabetes, a common problem is spread of misleading information by unqualified people. This concerning trend makes it more difficult for patients to receive prompt and proper medical advice, which in turn further delays their referral to nephrologists and endocrinologists. In this communication, we highlight the challenges and consequences of this burning issue. We also propose the steps that various stakeholders and policy makers should take to contain this issue at the earliest. Keywords: Chronic kidney disease. Community health, Diabetes, Health education, Quinary prevention.